2004
DOI: 10.1080/00016470410001222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyethylene and TiAIV wear particles on expression of RANK, RANKL and OPG mRNA

Abstract: Background Wear debris has been associated with periprosthetic osteolysis and loosening of total joint arthroplasties. RANKL (receptor activator of NF-κB ligand), RANK (receptor activator of NF-κB) and OPG (osteoprotegerin) are three key molecules which regulate differentiation, survival, fusion, and activation of osteoclasts.Material and methods We evaluated the effect of TiAlV and polyethylene particles on expression of RANK, RANKL and OPG mRNA. We used a human monocytic leukemic cell line (THP-1) in this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 29 publications
5
46
0
Order By: Relevance
“…Hatton et al (2003) on the other hand identified particles from ceramics in two magnitudes by a laser-based micro-dissection method (likewise on failing Mittelmeierprostheses), one group with a mean diameter of 0.503 µm, while the other group showed a diameter on the nanometre scale (24 ± 19 nm). The signalling pathways that have been investigated until now in cell-particle co-culture systems mainly contain cytokines (interleukins, TNF-α), prostaglandins and recently the RANK(L)/OPG-system, too, which so far, however, has only been tested on metallic and polyethylene particles (Baumann et al 2004) and not as yet on aluminium ceramics. On this occasion, an increased expression resp.…”
Section: In Vivo and In Vitro Studies On Wear Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hatton et al (2003) on the other hand identified particles from ceramics in two magnitudes by a laser-based micro-dissection method (likewise on failing Mittelmeierprostheses), one group with a mean diameter of 0.503 µm, while the other group showed a diameter on the nanometre scale (24 ± 19 nm). The signalling pathways that have been investigated until now in cell-particle co-culture systems mainly contain cytokines (interleukins, TNF-α), prostaglandins and recently the RANK(L)/OPG-system, too, which so far, however, has only been tested on metallic and polyethylene particles (Baumann et al 2004) and not as yet on aluminium ceramics. On this occasion, an increased expression resp.…”
Section: In Vivo and In Vitro Studies On Wear Particlesmentioning
confidence: 99%
“…More often particle studies have been carried out with THP-1 cells using other substances than PMA for the stimulation to macrophage-like cells. A research group from Würzburg, Germany, used THP-1 cells which had been pre-treated by a granulocyte macrophage colony-stimulating-factor (GM-CSF) and vitamin D 3 (Baumann et al 2004). …”
Section: 41mentioning
confidence: 99%
“…In detail, wear debris stimulates macrophage and other inflammatory cells to produce inflammatory cytokines, such as interleukin (IL)-1, IL-6, and TNF-α [4]. These inflammatory cytokines stimulate osteoblasts and stromal cells to produce large amounts of receptor activator of NF-КB ligand (RANKL) [5][6][7], a key player in initiating enhanced osteoclastogenesis and osteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent of adverse reactions to wear debris is likely to be underestimated, as this was not an option on the revision report forms in the early phase of the National Joint Registry. Several reasons for revision are often given and categories are not mutually exclusive; aseptic loosening and other cited reasons including pain (22.0% of single-stage THR revisions) and lysis (15.6%) are often the result of reactions to wear debris [2,3]. Device failure may be due to a combination of mechanical failure, resulting in high wear, and adverse responses to the wear particles, due to use of potentially unsafe materials.…”
Section: Introductionmentioning
confidence: 99%